Biomechanical Comparative Study of Postoperative Achilles Pull-out Strength After Open Versus: Endoscopic Calcaneoplasty for Haglund's Syndrome. Issue 3 (14th September 2018) - Gonzalez, Tyler; Michalski, Max; Metzger, Melodie; Nelson, Trevor; Eberlein, Samuel; Pfeffer, Glenn
Category: Hindfoot Introduction/Purpose: The risk of Achilles avulsion is the limiting factor in return to full weight bearing and early activity following calcaneoplasty for Haglund's syndrome. The most commonly performed surgical procedure is an open calcaneoplasty through a posterior approach. Another option is an endoscopic decompression, which theoretically causes less disruption of the Achilles insertion, and allows a more rapid return to full weight bearing and activity. Despite this potential benefit no study has assessed the difference in Achilles tendon pull-out strength after open versus endoscopic techniques. The purpose of this study was to investigate those changes in a cadaveric model and provide objective data upon which to base postoperative recovery. Methods: Six matched pairs of cadaveric specimens(mid-tibia to toes) were randomly divided into two surgical groups.Group#1 was treated with an endoscopic decompression under fluoroscopic guidance using a 4 mm burr.Group#2 was treated with a traditional calcaneoplasty through a posterior approach using a microsaggital saw.The Achilles was repaired back to the calcaneus with two nonsabsorbable suture anchors in Group #2.Fouroscopic guidance was used to exactly match the amount of bone removed from each matched pair.Pre and post procedure true lateral x-rays were obtained in both groups to quantify bone loss.These radiographic images were imported into Matlab computational software(MathWorks, Inc., Natick, MA) for digital analysis. The distal aspect of each calcaneus was potted and held at a 20 degree angle.The Achilles tendon was secured in a freeze-clamp, which was attached to a mechanical testing system. Specimens were then loaded to failure. Outcome measures include: Height of bony resection, angle of bone resection and load to failure. Results: To date our results show significantly higher pullout forces in specimens that had an endoscopic calcaneoplasty (average failure load: 1368 ±445 N) compared to those that received an open surgical procedure (450±184 N), p<0.05. On average, the endoscopic technique had a 204% greater pull out strength compared to the open cohort. The calcaneal resection angle (37 degrees vs 39 degrees, p=.6) and the height of bony resection (49% vs 51%, p=.39) were not statistically significant between the open and endoscopic techniques. Conclusion: This study describes the first biomechanical comparison of Achilles pull-out-strength between open and endoscopic calcaneoplasty.The endoscopic-technique had 204%greater pull-out-strength compared to the open-technique.Even though equal amounts of bone were resected in each technique, the open-technique requires more disruption of the Achilles insertion to accommodate the saw.This marked difference in pull-out-strength demonstrates the vulnerability of the Achilles insertion following open treatment.Our results support protected weight-bearing and cautious return to activity following open surgery. Also an endoscopic-technique results in significantly increased post-surgical mechanical strength compared to an open-technique. Therefore, earlier weight-bearing and return to activity may be warranted after endoscopic calcaneoplasty.